A new test of advanced theory of mind: The "Strange Stories Film Task" captures social processing differences in adults with autism spectrum disorders. Issue 6 (11th March 2017) - Murray, Kim; Johnston, Kate; Cunnane, Helen; Kerr, Charlotte; Spain, Debbie; Gillan, Nicola; Hammond, Neil; Murphy, Declan; Happé, Francesca
Abstract : Real‐life social processing abilities of adults with autism spectrum disorders (ASD) can be hard to capture in lab‐based experimental tasks. A novel measure of social cognition, the "Strange Stories Film task' (SSFt), was designed to overcome limitations of available measures in the field. Brief films were made based on the scenarios from the Strange Stories task (Happé) and designed to capture the subtle social‐cognitive difficulties observed in ASD adults. Twenty neurotypical adults were recruited to pilot the new measure. A final test set was produced and administered to a group of 20 adults with ASD and 20 matched controls, alongside established social cognition tasks and questionnaire measures of empathy, alexithymia and ASD traits. The SSFt was more effective than existing measures at differentiating the ASD group from the control group. In the ASD group, the SSFt was associated with the Strange Stories task. The SSFt is a potentially useful tool to identify social cognitive dis/abilities in ASD, with preliminary evidence of adequate convergent validity. Future research directions are discussed. Autism Res 2017 . © 2017 International Society for Autism Research, Wiley Periodicals, Inc. Autism Res 2017, 10: 1120–1132 . © 2017 International Society for Autism Research, Wiley Periodicals, Inc.